(untitled) (Tanzania Journal for Population studies and Development, 2017)
This paper discusses how social actors engage with the notion of race and religion in private spheres. It specifically shows how young people use religion to rationalise their dating preferences, and in so doing are inclined to heighten the existing ethno-racial boundaries. The interview excerpts used as examples in this paper are drawn from an ethnographic study that I conducted in Dar es Salaam and Mbeya from 2012-2015. In this paper I demonstrate that the common knowledge and personal experiences of secondary school students—with regards to norms and values of self and others—tend to influence their choice of dating partners, their everyday experiences of being in an intimate relationship, and their overall opinion of inter-racial marriages. Also, whereas closed groups such as the Balouch and South Asian communities advocate for racial endogamy and perpetuate sexual double standards, teenagers from these groups use religion as a tool to manipulate given community norms and values.